2020
DOI: 10.4049/immunohorizons.2000048
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of DOCK11 to the Expansion of Antigen-Specific Populations among Germinal Center B Cells

Abstract: Germinal centers (GCs) are a structure in which B cell populations are clonally expanded, depending on their affinities to Ag. Although we previously isolated a characteristic protein called dedicator of cytokinesis 11 (DOCK11) from GC B cells, limited information is available on the roles of DOCK11 in GC B cells. In this study, we demonstrate that DOCK11 may contribute to the expansion of Agspecific populations among GC B cells upon immunization of mice. The lack of DOCK11 in B cells resulted in the lower fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Pax5 encodes the B-cell lineage-specific activator protein, which affects B-cell differentiation at the early stages ( Arseneau et al, 2009 ). DOCK11 regulates B-cell activation during immunization ( Sakamoto & Maruyama, 2020 ). TBX21 is known as a regulator of immune cell development and function ( Stolarczyk, Lord & Howard, 2014 ), while IL-10 has been shown to modulate inflammatory responses and is particularly important in maintaining intestinal microbe-immune homeostasis ( Neumann, Scheffold & Rutz, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pax5 encodes the B-cell lineage-specific activator protein, which affects B-cell differentiation at the early stages ( Arseneau et al, 2009 ). DOCK11 regulates B-cell activation during immunization ( Sakamoto & Maruyama, 2020 ). TBX21 is known as a regulator of immune cell development and function ( Stolarczyk, Lord & Howard, 2014 ), while IL-10 has been shown to modulate inflammatory responses and is particularly important in maintaining intestinal microbe-immune homeostasis ( Neumann, Scheffold & Rutz, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we also described that adoptive transfer of cognate T cells recovered the impaired recall responses of antigen-experienced B cells in DOCK11-deficient mice. We have recently demonstrated that the lack of DOCK11 in B cells is involved in the impaired induction of T follicular helper, T FH cells upon immunization [ 11 ]. These T cells are an interesting and indispensable population since it has been known that these cells were found to provide cognate help in recall responses of memory B cells [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We successively demonstrated that DOCK11 was associated with bone marrow B cell development and marginal zone B cell formation [ 10 ]. In addition to this function, we recently also found that DOCK11 potentially contributes to the expansion of antigen-specific populations among GC B cells upon immunization [ 11 ]. Mechanistically, the lack of DOCK11 resulted in the attenuation of B cell-intrinsic signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DOCK11, a mediator of cytokinesis, is another contributor of immunosenescence during ageing, although independent of B cell antibody responses [ 38 ]. For instance, mice with DOCK11-deificient B cells have reduced antigen-specific participation in germinal centers, which is accompanied by lower B cell intrinsic-signaling stimulation [ 39 ]. Furthermore, the interleukin-1 converting enzyme CASP1, is a protease which converts the inactive form of IL-1Β to its active form, that is a precursor of inflammatory processes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%